2015
DOI: 10.1097/inf.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Borrelial Lymphocytoma in Children

Abstract: BL in children, treated with recommended antibiotics, is a mild disease with a good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Our results in 144 consecutive adult patients with BL diagnosed in a single center during a period of 29 years showed that most of the pretreatment clinical characteristics were similar to those in previous reports. All our patients had solitary BL, which is not surprising given that after the recognition of LB only 2 cases of multiple BL lesions, both in children, have been reported [20,34]. BL was located on the breast in 106 of our 144 patients (73.6%), on the ear lobe in 27 (18.8%), and at other locations in 11 (7.6%), substantiating previous findings that in adults BL is predominantly localized on the breast in the region of the areola mammae.…”
Section: Treatment Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our results in 144 consecutive adult patients with BL diagnosed in a single center during a period of 29 years showed that most of the pretreatment clinical characteristics were similar to those in previous reports. All our patients had solitary BL, which is not surprising given that after the recognition of LB only 2 cases of multiple BL lesions, both in children, have been reported [20,34]. BL was located on the breast in 106 of our 144 patients (73.6%), on the ear lobe in 27 (18.8%), and at other locations in 11 (7.6%), substantiating previous findings that in adults BL is predominantly localized on the breast in the region of the areola mammae.…”
Section: Treatment Resultsmentioning
confidence: 97%
“…Thus, in the 29-year period of the present study, EM was diagnosed in >16 000 adult patients but BL in only 144 at our LB Outpatient Clinic, which equates to about 550 and 5 cases per year, respectively. At the same institution, 33 children <15 years old were identified with BL in a period of 7 years (2008-2014), which is also about 5 cases per year [34]; however, this age group represents <15% of the Slovenian population.…”
Section: Treatment Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelial lymphocytoma is a rare skin manifestation characterized by a painless bluish-red nodule, which is predominantly reported in children 82. Typically, borrelial lymphocytoma is localized on the ear lobe, nipple, or scrotum.…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…In the case of borrelial lymphocytoma, a substantial increase in the number of IgG antibodies can be detected in the serum regardless of the length of infection [ 65 ], [ 76 ]. In rare cases, multiple borrelial lymphocytomas can occur in the early disseminated stages or even in the late stages of the disease.…”
Section: Clinical Manifestations Of Lyme Borreliosismentioning
confidence: 99%